Development and production of cabbage (Brassica oleracea var. Royal vantage) under different osmotic pressures and biofertilized with bacterial consortia - Aguilar-Flores, Iris Margarita; Espinosa-Victoria, David; Carcaño-Montiel, Moisés; Rodríguez-Mendoza , María de las Nieves (REVISTA TERRA LATINOAMERICANA, 2021)
The development and production of cabbage (Brassica oleracea var. Royal vantage) in a greenhouse, under different osmotic pressures of the Steiner nutrient solution and biofertlized with bacterial consortiums, were evaluated. A 4 × 3 factorial design was established, where the factors were four levels of osmotic pressure (0.18, 0.36, 0.54 atm and a control without nutrient solution), and two bacterial consortia: Azospirillum brasilense + Acinetobacter calcoaceticus (AA) and Raoultella terrigena + Chromobacterium violaceum (RC), and an uninoculated control. Six repetitions were established for each treatment. Seeds inoculated with the consortium AA had the highest emergence percentage (100%), as well as the highest emergence rate (20.5), compared with the consortium RC and the non-inoculated plants. Inoculation with the consortium AA and the osmotic pressure of 0.54 atm produced taller plants (60-65%), and a stem with a larger diameter (35-46%). The weight of the fresh biomass and the accumulation of dry material doubled in the inoculated plants compared to the non-inoculated ones. A higher concentration of K was observed in plants inoculated with AA and RC (20‑35% and 25-45%, respectively) compared to non-inoculated plants. The nitrate concentration in the plants increased between 200-350% and 60-230% with the inoculation of consortia AA and RC, respectively. The P concentration increased between 200-500% with the consortium AA and between 100-400% with the consortium RC. Inoculation with the consortia AA and RC, at osmotic pressure of 0.54 atm, induced the greatest development of the cabbage heads (classif ied as 5 and 4, respectively). It is concluded that cabbage, under moderate mineral fertilization in a greenhouse, responds favorably to the inoculation of plant growth promoting bacteria.